2016
DOI: 10.1016/j.bpsc.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Altered Neural Processing to Social Exclusion in Young Adult Marijuana Users

Abstract: Previous studies have reported that peer groups are one of the most important predictors of adolescent and young adult marijuana use, and yet the neural correlates of social processing in marijuana users have not yet been studied. In the current study, marijuana-using young adults (n = 20) and non-using controls (n = 22) participated in a neuroimaging social exclusion task called Cyberball, a computerized ball-tossing game in which the participant is excluded from the game after a pre-determined number of ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Emerging studies have suggested that functional coupling between ACC and frontal cortex corresponds with less efficient inhibitory processing 75 . This is relevant because the anterior cingulate has been implicated in social processing, including for cannabis users 76 . Further, the connection between frontal and cingulate cortical regions has also been involved in children’s neural processing of feedback from their parents 77 ; similar substrates are likely to be involved in clinical, dyadic exchanges with a therapist.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have suggested that functional coupling between ACC and frontal cortex corresponds with less efficient inhibitory processing 75 . This is relevant because the anterior cingulate has been implicated in social processing, including for cannabis users 76 . Further, the connection between frontal and cingulate cortical regions has also been involved in children’s neural processing of feedback from their parents 77 ; similar substrates are likely to be involved in clinical, dyadic exchanges with a therapist.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, 47 stress increased cannabis craving in dependent participants, confirming the important role of stress as a driving factor of dependence and relapse. 15 Against our expectations, however, the groups did not differ with respect to the subjective stress experience (however, one study reported a normal distress experience in cannabis users during social exclusion), 48 cardiovascular indices, self-perceived performance or task enjoyment. Together, these findings suggest that while stress induction and stress perception may be intact in dependent cannabis users, psychosocial stress increases cannabis craving and leads to marked deteriorations in cognitive performance.…”
Section: Discussionmentioning
confidence: 66%
“…In line with previous studies, 47 stress increased cannabis craving in dependent subjects, confirming the important role of stress as a driving factor of dependence and relapse. 15 Against our expectations, however, the groups did not differ with respect to subjective stress experience (however, one study reporting a normal distress experience in cannabis users during social exclusion), 48 cardiovascular indices as well as self-perceived performance or task enjoyment. Together this suggests that while stress induction and the perception thereof may be intact in dependent cannabis users, psycho-social stress increases cannabis craving and leads to marked deteriorations in cognitive performance.…”
Section: Discussionmentioning
confidence: 68%